2007
DOI: 10.1097/01.aog.0000250473.99575.72
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Translucency and the Risk of Congenital Heart Disease

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…14,15 Our findings that fewer than 5% of CCHDs had an NT >3.5 mm and that fewer than 10% were detected by the 99th percentile cutoff are lower estimates than others have observed. 11,13,28,29 These findings are consistent with previous studies that have demonstrated CCHD detection rates to be lower in low risk or general populations and lower with better CCHD ascertainment, both of which are characteristics of this study. 11,13,28,29 Given that our observed prevalence of 2.5 CCHD per 1000 births is similar to that reported across these same subtypes of CCHDs in both national and California specific studies, we believe that our ascertainment was robust.…”
Section: Commentsupporting
confidence: 93%
See 2 more Smart Citations
“…14,15 Our findings that fewer than 5% of CCHDs had an NT >3.5 mm and that fewer than 10% were detected by the 99th percentile cutoff are lower estimates than others have observed. 11,13,28,29 These findings are consistent with previous studies that have demonstrated CCHD detection rates to be lower in low risk or general populations and lower with better CCHD ascertainment, both of which are characteristics of this study. 11,13,28,29 Given that our observed prevalence of 2.5 CCHD per 1000 births is similar to that reported across these same subtypes of CCHDs in both national and California specific studies, we believe that our ascertainment was robust.…”
Section: Commentsupporting
confidence: 93%
“…11,13,28,29 These findings are consistent with previous studies that have demonstrated CCHD detection rates to be lower in low risk or general populations and lower with better CCHD ascertainment, both of which are characteristics of this study. 11,13,28,29 Given that our observed prevalence of 2.5 CCHD per 1000 births is similar to that reported across these same subtypes of CCHDs in both national and California specific studies, we believe that our ascertainment was robust. 30,31 Our period of ascertainment extended through 1 year of age, whereas others have included mostly only CCHDs that were diagnosed at birth.…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…8 An increased nuchal-translucency measurement is also useful for predicting other abnormalities such as congenital heart disease. [11][12][13] Therefore, obtaining the nuchal-translucency measurement is an important aspect of prenatal care. Our study has demonstrated that, although nuchal translucency can be visualized as optimally in the obese compared with the nonobese patient, there is a significant increase in the resources needed to obtain an optimal view.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In addition, an increased nuchal-translucency measurement has been associated with fetal cardiac defects, leading to the recommendation of following up increased nuchal-translucency measurements with fetal echocardiography. [11][12][13] Secondary to the importance of obtaining the nuchaltranslucency measurement and visualizing the nasal bone, we proposed a study to investigate the effect of increased BMI on the first-trimester ultrasound examination for aneuploidy risk assessment.…”
Section: Level Of Evidence: IImentioning
confidence: 99%